2016
DOI: 10.1089/aid.2015.0215
|View full text |Cite
|
Sign up to set email alerts
|

HIV Drug Resistance Among Children Initiating First-Line Antiretroviral Treatment in Uganda

Abstract: Background: There are limited data on primary human immunodeficiency virus drug resistance (HIVDR) in pediatric populations. This study aimed to assess the prevalence of primary HIVDR and associated risk factors among children initiating first-line antiretroviral therapy (ART) in Uganda.Methods: At three Ugandan clinics, children (age <12 years) requiring ART were recruited between January 2010 and August 2011. Before starting ART, blood was collected for viral load and pol gene sequencing. Drug resistance mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…Among 2014 samples with available clinical information, infants with PMTCT exposure had a higher prevalence and significantly stronger drug resistance than those without, which is consistent with other studies from the region [14, 17] . However, we did not find a correlation between age and prevalence of drug resistance [14] .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Among 2014 samples with available clinical information, infants with PMTCT exposure had a higher prevalence and significantly stronger drug resistance than those without, which is consistent with other studies from the region [14, 17] . However, we did not find a correlation between age and prevalence of drug resistance [14] .…”
Section: Discussionsupporting
confidence: 86%
“…However, we did not find a correlation between age and prevalence of drug resistance [14] . As in prior studies, some children with no reported PMTCT exposure still had resistance, indicating a direct transmission of resistant viruses from mother to child had occurred [14, 17] . We were unable to determine if resistance originated in the mother or arose de novo in the infant.…”
Section: Discussionmentioning
confidence: 79%
“…Study methods of this cohort have previously been described in detail. 12 We enrolled HIV-infected children aged ≤12 years from January 2010 to August 2011. For this analysis, participants starting on first-line ART were included and followed up for 24 months.…”
Section: Methodsmentioning
confidence: 99%
“… 11 Our group has previously shown high rates of HIV drug resistance among children initiating ART in Uganda. 12 …”
Section: Introductionmentioning
confidence: 99%
“…La prevalencia total de mutaciones de resistencia (28,6%) y la de resistencias primarias (11,1%) en la población analizada es similar a la descrita en la región y en el mundo, pero fue más elevada en los casos de resistencia secundaria (60%) 23,[31][32][33][34][35][36][37] .…”
Section: Discussionunclassified